Maize value chain potential in Ethiopia: Constraints and opportunities for enhancing the system - Rashid, Shahidur; Getnet, Kindie; Lemma, Solomon (International Food Policy Research Institute, 2010)
This report reaffirms that maize continues to be a significant contributor to the economic and social development of Ethiopia. As the crop with the largest smallholder coverage at 8 million holders (compared to 5.8 million for teff and 4.2 million for wheat), maize is critical to smallholder livelihoods in Ethiopia. In addition, maize is the staple crop with the greatest production at 4.2 million tons in 2007/08, compared to teff at 3.0 million tons and sorghum at 2.7 million tons1.